Translation of Phaedrus' Speech in Plato's Symposium (Pl. Smp. 178a-180c) - Pio, Fernanda Israel; Cornelli, Gabriele; Pitombo Bacelar, Agatha (Revista Archai, 2024)
In Plato's Symposium, Phaedrus is recognized as the "father of discourse" and occupies the first seat on the left. He introduces the theme of love, commencing his discourse with a series of references to tradition, including figures like Hesiod, Acusilaus, and Parmenides, to extol Eros. Phaedrus underscores the role of love in war, politics, and amorous relationships, emphasizing how love motivates humans to act exceptionally. His argument culminates in the notion that the pinnacle of love is the willingness to die for those we love. He illustrates this perspective with examples of couples: Alcestis and Admetus, Orpheus and Eurydice, and Achilles and Patroclus, demonstrating how love is inherently linked to death and how this sacrifice is rewarded by the gods. This translation highlights specific terms used in pederastic contexts, such as erastes and eromenos, through transliteration, distinguishing them from more generic terms for lovers and loved ones. The introduction briefly addresses how the understanding of pederastic relationships and issues related to the gender of the characters can influence the interpretation of the discourse. This translation invites readers to undertake a meticulous analysis of Phaedrus's discourse, exploring the complexities discussed and their implications for the understanding of love in Plato's work.